The relationship between parental intimacy quality and young children’s emotional and behavioral problems: the chain mediating role of parenting stress and parent-child relationship - Jiang, Ying; Zhang, Jing; Shi, Konghui; Wang, Xiaofen (Frontiers in Psychiatry, 2025)
IntroductionYoung children’s emotional and behavioral problems represent a significant public health concern globally. This study investigated the underlying mechanisms of parental intimacy quality and young children’s emotional and behavioral problems, focusing on the roles of parenting stress and parent-child relationship. We hypothesized that: (1) Parenting stress plays a mediating role in the relationship between parental intimacy quality and young children’s emotional and behavioral problems; (2) Parent-child relationship plays a mediating role in the relationship between parental intimacy quality and young children’s emotions and problem behaviors; (3) Parenting stress and the parent-child relationship play a chain mediating role in the relationship between parental intimacy quality and young children’s emotional and behavioral problems.MethodAn online survey was administered to 1868 young children’s parents in Fujian province, China, using convenience sampling methods. Data were analyzed using structural equation modeling (SEM) with the software Mplus 7.4 to examine the relationships between parental intimacy quality, parenting stress, parent-child relationship and young children’s emotional and behavioral problems.ResultsThe findings indicated that (1) parenting stress plays a mediating role in the relationship between parental intimacy quality and young children emotional and behavioral problems; (2) parent-child relationship plays a mediating role in the relationship between parental intimacy quality and young children emotional and behavioral problems; (3) parenting stress and parent-child relationship play a chain mediating role in the relationship between parental intimacy quality and young children’s emotional and behavioral problems.ConclusionOur study highlights the close relationship between parental intimacy quality and young children’s emotional and behavioral problems, in which context parenting stress and parent-child relationship play a vital role.